(untitled) (Journal of Nobel Medical College, 2018)
Background : Normal resolution time of pneumonia is variable. Non-resolving pneumonia is a challenging clinical problem. Etiological, patient and treatment-related factors affect outcomes. Bronchoscopy is initial diagnostic technique in evaluating these patients. The study explored the utility of bronchoscopy in diagnosing of non-resolving pneumonia. Material and Methods: Records of the patients diagnosed with non-resolving pneumonia who underwent bronchoscopy from 20th January 2017 to 19th January 2018 were analysed. The data analyzed included demographic characteristics, clinical profile, bronchoscopic findings, chest imaging, and hospital discharge status. Non-resolving pneumonia was defined as focal infiltrates with symptoms of acute pulmonary infection and lack of clinical and radiological improvement within 12 weeks despite a minimum of 10 days treatment. For analysis descriptive statistics like mean and percentage and tabular and graphical presentation were made. Results: Forty-five patients had non resolving Pneumonia. A total 75.0% were males with age range of 25 to 85 years and commons symptom were cough with fever (75.0%) followed by hemoptysis, chest pain, and breathlessness. Bronchoscopically multiple ulcerated lesions, inflamed tracheobronchial tree with mucopurulent secretions and mass lesions were common. Etiologically 66.6 % patients had TB, followed by lung cancer, bronchiectasis and pneumonia. Conclusion: Bronchoscopy has better utility and is the diagnostic modality of choice in establishing etiology of non-resolving pneumonia. Journal of Nobel Medical College Volume 7, Number 1, Issue 12, January-June 2018, page : 1-5